Abnormal transcriptome-wide DNA demethylation induced by folate deficiency causes neural tube defects - Wang, Shan; Zeng, Yubing; Pei, Pei; He, Xuejia; Liu, Fan; Zhang, Ting (Frontiers in Genetics, 2022)
Neural tube defect (NTDs) is one of the most common and serious fetal and neonatal birth defects. Neural tube closure (NTC) is an exquisitely coordinated process and this procedure is influenced by both genetic and environmental factor. Folic acid (FA) supplementation is an effective for prevention of a proportion of NTDs, however, the mechanism remains unclear. In this study, our data demonstrated genome-wide enrichment of 5-hydroxymethylcytosine (5hmC) modification on active transcriptional start sites (TSS) and decreased 5-methylcytosine (5mC) binding to TSS under folate deficiency in mESCs (mouse embryonic stem cells). Furthermore, folate deficiency promoted 5hmC enrichment enhancer histone 3 lysine 27 acetylation (H3K27ac) binding to Shh pathway genes in mESCs. Upregulation of Shh target genes was observed in mouse brain tissue under low levels of maternal serum folate, along with increased expression of 5-methylcytosine dioxygenase Tet1 levels. Taken together, we found that folate deficiency promoted DNA demethylation and enriched 5hmC through recruitment of H3K27ac to activate the Shh signaling pathway. These results suggest that the 5hmC modification increases concomitantly with a positive correlation to Shh gene expression in folate deficiency-induced mouse NTDs.